APOPTOTIC AND CYTOTOXIC ACTIVITIES OF STROBILANTHES VIRENDRAKUMARANA VENU AND P. DANIEL IN ALLIUM CEPA AND HUMAN RED BLOOD CELLS - RESHMI C; THOPPIL JE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was aimed to explore the cytotoxicity of the aqueous shoot extract of Strobilanthes virendrakumarana Venu and P. Daniel in Allium cepa and human erythrocytes. It also focuses on the efficacy of the extract to induce apoptosis in the root primordia of A. cepa. Methods: The aqueous extract of the shade-dried shoot was prepared. The cytotoxicity was evaluated both in A. cepa and human red blood cells (RBC) using standard protocols. The apoptotic and metabolic/mitochondrial activity evaluated with the help of Evans blue staining and 2,3,5-Triphenyl tetrazolium chloride (TTC) staining methods, respectively. Results: Cytotoxic assay unveiled different types of aberrations which were dose-dependent. RBC assay revealed the capacity of phytocompounds in the extract to interact with the osmotic balance of RBC membrane and thereby modify it. Apoptosis induction was detected in A. cepa roots treated with various concentrations of the plant extract. The gradation in stain uptake indicates the apoptotic activity of the plant extract. The amount of generated formazon in TTC staining is an indirect evaluation of the metabolic/mitochondrial activity of the cell. Conclusions: These results may be attributed to the presence of bioactive compounds in the plant extract. The staining techniques reveal the qualitative and quantitative evaluation of the potentiality of the extract. Thus, the present study opens a new avenue for further exploration of the plant for its bioactivities.